Effect of ABT-263 on Intestinal Fibrosis in Human Myofibroblasts, Human Intestinal Organoids, and the Mouse Salmonella typhimurium Model. Issue 2 (1st February 2022) - Johnson, Laura A; Rodansky, Eva S; Tran, Anhdao; Collins, Stephen G; Eaton, Kathryn A; Malamet, Benjamin; Steiner, Calen A; Huang, Sha; Spence, Jason R; Higgins, Peter D R
Abstract : Lay Summary: Intestinal fibrosis is a common complication of Crohn's disease, yet no effective therapies exist to treat fibrostenotic disease. We report ABT-263 (navitoclax) reduces intestinal fibrosis in in vitro models and reduces inflammation and fibrosis in a mouse IBD model.